2014
DOI: 10.1097/sla.0000000000000560
|View full text |Cite
|
Sign up to set email alerts
|

The NOTA Study (Non Operative Treatment for Acute Appendicitis)

Abstract: Antibiotics for suspected acute appendicitis are safe and effective and may avoid unnecessary appendectomy, reducing operation rate, surgical risks, and overall costs. After 2 years of follow-up, recurrences of nonoperatively treated right lower quadrant abdominal pain are less than 14% and may be safely and effectively treated with further antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
106
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(114 citation statements)
references
References 35 publications
5
106
1
2
Order By: Relevance
“…Long-term follow-up from non-randomized trials and observational studies, lasting up to 7 years, does not demonstrate higher rates of recurrence [37]. The recently published NOTA study demonstrated a success rate of 83% for NOM after a 2-year follow-up [38]. The mean time for recurrence was after approximately 4 months, therefore suggesting that longer follow up-periods do not necessarily lead to significantly higher rates of recurrent disease.…”
Section: Why Do Not Remove All Of Them?mentioning
confidence: 99%
“…Long-term follow-up from non-randomized trials and observational studies, lasting up to 7 years, does not demonstrate higher rates of recurrence [37]. The recently published NOTA study demonstrated a success rate of 83% for NOM after a 2-year follow-up [38]. The mean time for recurrence was after approximately 4 months, therefore suggesting that longer follow up-periods do not necessarily lead to significantly higher rates of recurrent disease.…”
Section: Why Do Not Remove All Of Them?mentioning
confidence: 99%
“…A non-inferiority analysis will be performed to compare the primary and secondary outcomes. Based on current adult literature, the treatment efficacy difference between operative and non-operative treatment is about 25–35% 11–19. The most recent RCT in adults used 25% as its non-inferiority margin 19.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies, systematic reviews and meta-analyses have demonstrated that antibiotics are a safe and effective treatment for AUA in adults 11–19. The Appendicitis Acuta (APPAC) multicentre, open-label, non-inferiority, randomised controlled trial (RCT) in adults reported a significantly lower overall complication rate of 2.8% in the NOM group, compared with 20.5% in patients who received operative management (OM).…”
Section: Introductionmentioning
confidence: 99%
“…1,20 Most studies have been performed in patients with only uncomplicated appendicitis. However, Hansson et al 21 conducted a randomized clinical trial aimed at unselected patients.…”
Section: Discussionmentioning
confidence: 99%
“…13 The reported recurrence rates vary widely from 5% to 37%. 4 Some authors have also suggested that there is a risk of potentially missing a diagnosis for the patients treated nonoperatively because there is no surgical exploration and therefore no specimens retrieved for pathologic examination.…”
Section: Introductionmentioning
confidence: 99%